Prevalence and relevance of abnormal glucose metabolism in acute coronary syndromes: insights from the PLATelet inhibition and patient outcomes (PLATO) trial - Åkerblom, Axel; Wojdyla, Daniel; Steg, Philippe Gabriel; Wallentin, Lars; James, Stefan K.; Budaj, Andrzej; Katus, Hugo; Himmelmann, Anders; Huber, Kurt; Siegbahn, Agneta; Storey, Robert F.; Becker, Richard C. (Journal of thrombosis and thrombolysis, 2019)
Diabetes mellitus (DM) and abnormal glucose metabolism are associated with cardiovascular (CV) disease. We investigated the prevalence and prognostic importance of dysglycaemia in patients with acute coronary syndromes (ACS) in the PLATelet inhibition and patient Outcomes (PLATO) trial. Diabetes was defined as known diabetes or HbA1c ≥ 6.5% or non-fasting glucose ≥ 11.1 mmol/L on admission, prediabetes as HbA1c ≥ 5.7% but < 6.5%, and no diabetes as HbA1c < 5.7%. The primary endpoint was the composite of CV death, spontaneous myocardial infarction type 1 (sMI) or stroke at 12 months. Multivariable Cox regression models, adjusting for baseline characteristics, and biomarkers NT-proBNP and troponin I, were used to explore the association between glycaemia and outcome. On admission, 16,007 (86.1%) patients had HbA1c and/or glucose levels available and were subdivided into DM 38.5% (6160) (1501 patients had no previous DM diagnosis), prediabetes 38.8% (6210), and no DM 22.7% (3637). Kaplan Meier event rates at 12 months for CV death, sMI or stroke per subgroups were 14.5% (832), 9.0% (522), and 8.5% (293), respectively with multivariable adjusted HRs, versus no diabetes, for diabetes: 1.71 (1.50-1.95) and for prediabetes 1.03 (0.90-1.19). Corresponding event rates for CV death were 6.9% (391), 3.4% (195) and 3.0% (102), respectively, with adjusted HRs for patients with DM of: 1.92 (1.42-2.60) and for prediabetes 1.02 (0.79-1.32). Abnormal glucose metabolism is common in ACS patients, but only patients with definite DM have an increased CV risk, indicating that prediabetes is not immediately associated with worse CV outcomes.
Gesehen am 05.02.2020